2016
DOI: 10.1007/s13402-016-0267-7
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule inhibitors of FGFR, integrins and FAK selectively decrease L1CAM-stimulated glioblastoma cell motility and proliferation

Abstract: We here show for the first time that small-molecule inhibitors of FGFR, integrins and FAK effectively and selectively abolish L1-stimulated migration and proliferation of glioblastoma-derived cells. Our results suggest that these inhibitors have the potential to reduce the aggressiveness of high-grade gliomas expressing L1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 64 publications
5
44
0
Order By: Relevance
“…The interface allows user control over a variety of parameters. By using data collected over a range of experimental conditions (e.g., [ 1 ]) one can adjust the parameters in the model to produce simulated behavior similar to the experimental behavior observed in the laboratory.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The interface allows user control over a variety of parameters. By using data collected over a range of experimental conditions (e.g., [ 1 ]) one can adjust the parameters in the model to produce simulated behavior similar to the experimental behavior observed in the laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…The recurring tumors often are even more aggressive in their spread, resulting in the extremely poor prognosis typical of GBM. We have shown that the neural adhesion molecule L1CAM (L1) stimulates GBM cell motility and invasion both in vitro and in vivo using a variety of approaches [ 1 , 10 , 17 ]. If mechanisms controlling GBM cell motility and invasion can be modeled and simulated, then this likely will aid in experimental design and predicting outcomes of experimental manipulations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell adhesion receptors other than integrins, including L1CAM, also can promote cell migration [reviewed in [13]]. L1CAM binds to RGD-peptide-binding integrins, including integrin αvβ3 due to the presence of an RGD-peptide in its extracellular sixth Ig domain and this peptide appears to be necessary for the pro-migratory and pro-invasive effects of L1CAM in cancer cells [1318]. …”
Section: Introductionmentioning
confidence: 99%